EDM process through mathematical model - Dana Dehghani; Azli Yahya; Nor Hisham Khamis; Ali Idham Alzaidi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
EDM is a well-established hole machining option with various advantages due to non-contact characteristics of the process. However, knowledge about the process is not enough for its more improvements. Exprimenal studies are costly and time consuming because of the complex nature of process. Therefore, process modeling is a good alternative to reduce the experimental expense related to the technology. This paper studys EDM process through mathematical model, which includes the precise insight into the interactive behavior of EDM system. The ignition, discharge and recovery phases of the model have been developed through MATLABs time domain analysis. Simulation result shows good agreement with expected profile of EDM spark. To verify the model, simulated material removal rates (MRRs) from series of simulation are compared with the experimental ones reported by previous researcher. Ability of the model to predict the dynamic behavior profile of the EDM system is successfully confirmed by low average percentage error in predicting MRR.